Optimalisasi Penanganan Sampah Organik dan Efektivitas Penggunaan Maggot dalam Pengurangan Volume Sampah di Perkotaan - Prasetiyo, Teguh (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2025)
The problem of organic waste in urban areas is increasing with population growth and consumer activity. Suboptimal management has the potential to cause environmental pollution and health problems. This study aims to assess the effectiveness of using Black Soldier Fly (BSF) maggots in reducing the volume of organic waste and producing economically valuable biomass. The research method was conducted through an experimental design with three types of organic waste: vegetables, fruits, and food waste, each with an initial weight of 10 kg. The results showed that maggots were able to reduce organic waste with an average reduction of 65%. Food waste showed the highest reduction of 70% and produced 1,450 grams of maggot biomass, while fruit had the lowest reduction (60%) with a biomass of 1,100 grams. These findings indicate a positive correlation between waste reduction effectiveness and maggot biomass productivity. The results support the notion that maggot-based bioconversion technology can be an alternative solution for organic waste management in urban areas, while supporting the concept of a circular economy and sustainable development.